Dietary Characteristics of Eastern James Bay Cree Women - Delormier, Treena; Kuhnlein, Harriet V. (ARCTIC, 1999)
Food use and nutrient intake were studies with Cree women of Wemindji and Eastmain, Quebec. During summer 1994 and winter 1995, 24-hour recalls and food frequency questionnaires were collected from 219 women of three age groups (20-40; 41-60; >60 years). While reported energy intakes were somewhat low, 94% of the women exceeded 2/3 of the recommended nutrient intake (RNI) for protein, and 80% exceeded 2/3 of the RNI for iron. However, 44% of the women reported calcium intakes of less than 1/2 the RNI. Mean total fat intake reported by young and middle adults was greater than 30% of total energy. Primary sources of fat were market food, indicating that education efforts targeting fat intake should emphasize market food choices. Species and amounts of traditional food consumed varied by season. The percentage of elders who consumed traditional food was significantly higher (p<0.001, Chi² = 29, Mantel-Haenzel) than those of traditional food users in the middle and young age groups. Dietary data for the James Bay Cree, which were lacking prior to this research, are important resources for those working in health and wellness with this population group and other aboriginal groups that use traditional food. On a étudié l'utilisation de la nourriture et l'apport nutritif chez des femmes cris de Wemindji et de Eastmain au Québec. Durant l'été de 1994 et l'hiver de 1995, on a recueilli des rappels de 24 heures sur les aliments et des questionnaires portant sur la fréquence de consommation de certains aliments auprès de 219 femmes appartenant à trois groupes d'âge (20 à 40, 41 à 60 et > 60 ans). Alors que les apports en énergie mentionnés étaient plutôt bas, 94 p. cent des femmes dépassaient les deux tiers de l'apport nutritionnel recommandé (ANR) en protéines, et 80 p. cent dépassaient les deux tiers de l'ANR en fer. Cependant, 44 p. cent des femmes ont déclaré des apports de calcium inférieurs à la moitié de l'ANR. La moyenne de l'apport total en gras rapporté par les jeunes adultes et les adultes d'âge moyen ...